Use of mobile applications in the self‑management of gestational diabetes mellitus: a narrative review - Garbacz, Anna Izabela; Kosiorek , Paweł; Radziwonka, Agnieszka; Wrochna, Bartłomiej Maciej; Olborska, Anna; Niezgoda, Ada; Stondzik, Gabriela; Majszyk, Tomasz; Głuski, Jacek; Brzozowska, Agnieszka; Borowiecka, Patrycja; Węglarz, Aleksandra (Journal of Education, Health and Sport, 2026)
INTRODUCTION AND PURPOSE: Gestational diabetes mellitus (GDM) is an increasingly common pregnancy‑related metabolic disorder associated with maternal and perinatal morbidity and an elevated long‑term risk of type 2 diabetes. Effective management relies on structured glucose monitoring, medical nutrition therapy and adequate physical activity, with pharmacotherapy required when lifestyle measures alone do not achieve glycaemic targets. Sustained self‑management is often difficult, particularly when access to specialist care and structured diabetes education is limited. Mobile health technologies offer new options to support daily GDM management. This narrative review summarises recent evidence on smartphone‑based applications for GDM self‑management, focusing on core functions, clinical effectiveness and patient‑reported outcomes, as well as key implementation challenges. BRIEF DESCRIPTION OF THE STATE OF KNOWLEDGE: GDM‑specific applications support glucose logging, graphical feedback, alerts, lifestyle counselling and secure communication with health‑care professionals. These tools appear feasible and acceptable, with high user satisfaction and reports of greater convenience, perceived support and better understanding of GDM. Quantitative data generally indicate non‑inferior glycaemic control compared with conventional care, with some improvements in postprandial glucose and selected maternal and neonatal outcomes, although the evidence base remains limited. SUMMARY (CONCLUSION): Available data support smartphone‑based applications as a promising adjunct to standard GDM care, reinforcing key elements of self‑management and enabling flexible remote surveillance. Further multicentre trials and detailed evaluation of features that sustain engagement and improve clinically meaningful outcomes are required, together with user‑centred design and careful integration of digital decision‑support into antenatal and postpartum diabetes care.